(untitled) (Journal of the College of Basic Education, 2022)
Theories have evolved so that they depend in their composition and applications on the individual’s willingness and the needs of society. They acquire technology that guarantees them publicity, and the nations that have passed for a long time in slumber and lethargy have awakened to the people’s right to education and the duty of the state to enable each of its members to have the opportunity to learn, and the nations that neglect the education of their children have become marked by backwardness and are limited to keeping pace with the progress of the material, scientific, social and cultural world .Perhaps the use of the principles of the Gestalt school and the way of insight in teaching the Arabic language is almost unique as an independent subject looking for how to use these principles to develop the teaching of the Arabic language to non-native speakers.